Evolution of structure and magnetic properties in PrCo5 magnet for high energy ball milling in ethanol*Project supported by the National Natural Science Foundation of China (Grant No. 51461033). (August 2015) - Li, Zhu-Bai; Lan, Jian-Ting; Zhang, Xue-Feng; Liu, Yan-Li; Li, Yong-Feng
Abstract High energy ball milling (HEBM) is employed to produce nano-sized grains and particles. In this paper, the structure and magnetic properties are investigated in PrCo5 alloy for HEBM in an ethanol milling medium. With the increase of milling time, the grain size reduces and the coercivity increases. For a milling time of less than 30 min, the hysteresis loop of the aligned sample is very different from that of the un-aligned sample and it does not show a large decrease in magnetization slope, indicating a relatively good alignment of easy axes in particles due to the fact that the texture is nearly well preserved. However, when the milling time is further prolonged, the textured structure deteriorates in the powders. Even though exchange coupling exists between grains within the particle, the magnetic properties are exchange-decoupled between particles and the dipolar interaction results in a negative value of δm in the whole range of the magnetic field.